Structure of Liver Sinusoid Endothelial Cells under the Conditions of General Cooling of Rats - Kaprelyants, A. S.; Marchenko, L. M.; Migunova, R. K. (Problems of Cryobiology and Cryomedicine, 2003)
As a result of the investigations performed there were obtained the novel scientific data on the effect of deep total hypothermia in rats on cell ultrastructure of liver sinusoids, as well as there have been calculated morpho- and stereometric characteristics of subcellular elements of endotheliocytes. It was shown the rise of cell reactivity in vascular endothelium of liver microcirculatory channel.